Global Product Development Proceedings of the 20th CIRP Design Conference, Ecole Centrale de Nantes, Nantes, France, 19th-21st April 2010 - Bernard, Alain (Springer eBooks., 2011)
This book of proceedings is the synthesis of all the papers, including keynotes presented during the 20th CIRP Design conference. The book is structured with respect to several topics, in fact the main topics that serve at structuring the program. For each of them, high quality papers are provided. The main topic of the conference was Global Product Development. This includes technical, organizational, informational, theoretical, environmental, performance evaluation, knowledge management, and collaborative aspects. Special sessions were related to innovation, in particular extraction of knowledge from patents.